Peran Pembinaan Anak dalam Meningkatkan Kemandirian Anak di Panti Asuhan Amrullah Kabupaten Gowa - Udas, Udas; Pratiwi, Nini; Hamdy, Musyawarah; Supiana, Ilham (Journal of Comprehensive Science, 2025)
An orphanage is a social institution that cares for children from underprivileged backgrounds in terms of family such as orphans, orphans and orphans and poor children. Orphanages are established to foster and educate and care for children so that they get a decent life both in terms of economy, social, and education for the future. Independence is an attitude of self that does not depend on others, viewing humans as a perfect physical and spiritual unity to be realized in life. Thus, the independence that a person has can be seen from two aspects, namely physical and spiritual aspects which are expressed in daily life activities, in addition to having internal factors such as child observation, fantasy and feelings while external factors such as the environment, educators/mentors. This factor determines the independence of children in orphanages is expected to have the ability of children to achieve maximum learning achievement, so that the success of children's learning can be achieved, namely children will get good learning achievement. This research is quantitative, with the total population of children, samples are taken from some children to represent the population studied. data collection techniques based on questionnaires and interviews, while for data analysis processing techniques are quantitative. The results of this study indicate that there is a very large role of orphanages in fostering children's mental health, education and skills development. This shows that orphanages play a role in fostering children's independence to prepare for a brighter future for children in facing their future lives.